O currículo na Educação Infantil a partir de experiências da vida cotidiana e dos direitos das crianças - Brunner, Lilian Murad (2025)
The childhood curriculum in Early Childhood Education is often presented as a opportunity for the integral development of children, but it often faces tensions between institutional proposals and teachers' pedagogical practices. In the light of these consideration, this investigation sought to understand how the childhood curriculum of a private school in the city of São Paulo is presented in school documents (School Curriculum and Teaching Plan) and how teachers evaluate this curriculum in practice. Based on the theories of Vygotsky, Moss, and Malaguzzi on childhood, and on the reflections of Arroyo, Sacritan, Imbérnon, and the National Common Curricular Base (NCCB) on curriculum, the approach of Critical-Collaborative Research (CCR) was adopted as a research method, analyzing documents and conducting questionnaires with teachers. The critical-reflexive analysis proposed by Liberali and the documentary analysis as proposed by Lüdck and André, allowed us to show that school document’s structure and implement the curriculum of childhoods according to the BNCC, which promotes meaningful and diversified experiences. Teachers' insights emphasized both the challenges and opportunities in implementing the curriculum, underlining the importance of a collaborative and supportive environment. The result of this research suggests that a curriculum that values children's experiences and rights, aligned with the BNCC guidelines and theories of child development, is essential to ensure quality and inclusive education, providing valuable contributions to improve educational practices in loco